2021
DOI: 10.37481/sjr.v4i3.330
|View full text |Cite
|
Sign up to set email alerts
|

Kredibilitas Celebrity Endorser Dan Minat Beli Penggemar Raffi Ahmad Dan Nagita Slavina Terhadap Skincare MS Glow

Abstract: The competition in the cosmetic industry business is getting tougher and more challenging for the perpetrators. To face this competition in order to continue to exist in the cosmetic market, business actors are actively hooking up customers by partnering with a number of celebrities. Business people are competing to like their cosmetic products by applying celebrity endorser services. This research was conducted with the aim of finding out how credible celebrity endorsers Raffi Ahmad and Nagita Slavina are in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Companies that use celebrities in their product advertisements consider many factors. Sokolova and Bobicev suggest that the use of such celebrities can sometimes increase sales, but there are times when it fails to promote the product [8]. Celebrity groups that are commonly used as advertising stars are artists, movie stars, singers, models, and even athletes who are known by the audience.…”
Section: Celebrity Endorsermentioning
confidence: 99%
“…Companies that use celebrities in their product advertisements consider many factors. Sokolova and Bobicev suggest that the use of such celebrities can sometimes increase sales, but there are times when it fails to promote the product [8]. Celebrity groups that are commonly used as advertising stars are artists, movie stars, singers, models, and even athletes who are known by the audience.…”
Section: Celebrity Endorsermentioning
confidence: 99%
“…For instance, research conducted by (Ramadhan et al, 2023;Choshaly & Mirabolghasemi, 2022) indicates that viral marketing has an impact on purchase intention. Furthermore, studies carried out by (Barokah et al, 2021;Ahmad et al, 2020;Singh et al, 2021) have shown that celebrity endorsers also have a significant effect on purchase intention.…”
Section: Introductionmentioning
confidence: 97%
“…MS Glow advertises its products with a well-known artist in Indonesia, namely NagitaSlavina [16] . With this, it aims to get the attention of the wider community who are considered to have the ability, quality, and strength that can create consumer confidence [17] .…”
Section: Introductionmentioning
confidence: 99%